Lithuanian partisans from political philosophy perspective - Adomėnas, Mantas (Genocidas ir rezistencija, 2006)
Is partisan struggle legal? What is the difference between partisans and terrorists? Where are the limits of the legitimacy of partisan activity and how should the Lithuanian partisans be evaluated from this point of view? The concept of partisan warfare is closely intertwined with descriptive and evaluative discourses of varying degrees and nature, especially in relation to terrorist activities. Thus, from the point of view of political philosophy, the Lithuanian partisans are a distinctive phenomenon. The partisans’ resistance movement is not only an attempt to wage a regular war under different circumstances and means. Their activities are generally characterised by the aspiration to re–establish the structures of statehood and legitimacy in an unconventional way. It is a kind of attempt to re–establish the rule of law in the Soviet anti–state, supported by the population, legitimately represented, etc. In general, the Lithuanian partisan struggle goes against the trends of the epoch and the direction of the evolution of partisan warfare. Their methods of warfare would be totally ineffective in controlling territory in the way permitted by modern technologies. It is becoming increasingly difficult to protect the islets of an alternative order (as well as the prospect of a regular resistance army) from them.